The advertisement call of the Hoogmoed’s harlequin toad Atelopus hoogmoedi Lescure, 1974 from northern Brazil (Anura, Bufonidae) - Costa-Campos, Carlos Eduardo; de Carvalho, Thiago Ribeiro (Zootaxa, 2018)
Harlequin toads (Atelopus) are distributed over a wide range in the Amazon Rainforest, mostly associated with streamlets in dense ombrophilous forests in lowland and sub-montane regions. Atelopus hoogmoedi Lescure, 1974a was considered as bearing full species status by Lötters et al. (2005), although until that moment this species had been assigned to a subspecies of A. pulcher (Boulenger, 1882) (Lescure 1974a, 1976) or of A. spumarius Cope, 1871 (Lescure et al. 1980; Lescure & Marty 2000; Lötters et al. 2002). More recently, Noonan & Gaucher (2005) subscribed to Lötters et al. (2005)’s statement that A. s. hoogmoedi should belong to a distinctive species (A. hoogmoedi), based on phylogeographic evidence. The species’ range is currently restricted to the Guiana Shield of French Guiana, Suriname, Guyana, and in adjacent regions of northern Brazil (Lötters et al. 2005).